Old Meany Hall being demolished, University of Washington, August 1965
Meany Hall was built in 1908 to serve as the auditorium for the Alaska-Yukon-Pacific Exposition. It was demolished in 1965 after suffering extensive damage in an earthquake. Handwritten on verso: Meany Hall. August, 1965. PH Coll 778